Direct routes to functional RAFT agents from substituted N-alkyl maleimides. Issue 45 (14th November 2022) - Catania, Rosa; Foralosso, Ruggero; Spanos, Lampros; Russo, Emanuele; Mastrotto, Francesca; Gurnani, Pratik; Butler, Kevin; Williams, Huw; Stolnik, Snow; Mantovani, Giuseppe
Abstract : Three different routes are presented for the synthesis of functional RAFT agents from N -substituted maleimides, which are then used to synthesise α, β, ω-functional RAFT polymers. Abstract : N -substituted maleimides have become an indispensable tool for the synthesis of bioconjugates and functional materials. Herein, we present three strategies for the incorporation of N -alkyl substituted maleimides into RAFT agents and show that these maleimide-derived CTAs can be used to easily introduce a range of chemical functionality at the β-position of polymer chains, resulting in α, β, ω-functional RAFT polymers. With both functional maleimides and RAFT agents that are increasingly available on the market, the approach presented in this study could facilitate the synthesis of end-functional macromolecules and will complement well the range of existing synthetic routes, including those utilising N -substituted maleimides, to functional polymeric materials.